Faktor-Faktor yang Memengaruhi Continuance Intention Penggunaan QRIS BRI Merchant oleh Pelaku UMKM di Jakarta - Daril Fajar Ardiyansyah; Diena Noviarini; Ringga Sentagi Asa (Indo Publishing, 2026)
This study aims to analyze the effects of perceived ease of use, perceived usefulness, and trust on the continuance intention to use QRIS BRI Merchant among Micro, Small, and Medium Enterprises (MSMEs) in DKI Jakarta, partially. This research employs a quantitative approach using a survey method and Structural Equation Modeling with a Partial Least Squares (SEM-PLS) technique. The sample consists of 160 MSME owners who use QRIS BRI Merchant in DKI Jakarta, selected through purposive sampling. The data were analyzed using SmartPLS software. The results indicate that: (1) perceived ease of use has a positive and significant effect on the continuance intention to use QRIS BRI Merchant; (2) perceived usefulness has a positive and significant effect on the continuance intention to use QRIS BRI Merchant; and (3) trust has a positive and significant effect on the continuance intention to use QRIS BRI Merchant. These findings highlight the importance of system usability, perceived benefits, and user trust in encouraging the sustained use of digital payment systems. This study is expected to provide practical insights for banking institutions to enhance the quality and reliability of QRIS services in order to support the long-term adoption of digital payment systems among MSMEs.